COVID-19 confinement impact on weight gain and physical activity in the older adult population: Data from the LOST in Lombardia study. (April 2022) - Stival, Chiara; Lugo, Alessandra; Bosetti, Cristina; Amerio, Andrea; Serafini, Gianluca; Cavalieri d'Oro, Luca; Odone, Anna; Stuckler, David; Iacoviello, Licia; Bonaccio, Marialaura; van den Brandt, Piet A.; Zucchi, Alberto; et al.
Summary: Background & aims: COVID-19 containment measures significantly impacted lifestyle of the general population, including physical activity. Although the older adults are particularly susceptible to the potential consequences of sedentary lifestyle and inactivity, few studies investigated pandemic effects in this segment of the population. We aimed to evaluate COVID-19 pandemic effects on weight gain and physical activity in the Italian older adults, and assess the impact of possible changes in physical activity on mental health wellbeing. Methods: In November 2020, a cross-sectional survey was conducted on a representative sample of 4400 older adults (aged 65 or more) from the Lombardy region, Northern Italy. Changes in body mass index (BMI) and physical activity were assessed, compared to the previous year. Using unconditional multiple logistic models, we estimated the odds ratios (OR) and the corresponding 95% confidence intervals (CI) of a decrease in physical activity during COVID-19 pandemic and we evaluated if decreased physical activity was a determinant of a worsening in psychological wellbeing. Results: Neither weight gain nor increase in obesity prevalence occurred during the pandemic. Mean time spent in physical activity significantly decreased, with 43.8% of participants reporting a decrease of 1 h/week or more during COVID-19 pandemic. A decreased physical activity was determinant of a worsening of selected mental health outcomes, such as: sleep quality (OR = 2.45; 95% CI: 1.91–3.15) and quantity (OR = 1.54; 95% CI: 1.18–2.02), anxiety (OR = 1.31; 95% CI: 1.14–1.52) and depressive symptoms (OR = 1.61; 95% CI: 1.38–1.88). Conclusion: During the COVID-19 pandemic, while no major changes in BMI were observed, physical activity significantly declined in the older adults. In this population, the lack of physical activity might have contributed to the observed worsening in mental health. During emergency periods, encouraging physical activity might be effective also to preserve psychological wellbeing.